Učinkovito sodno varstvo pred slovenskimi in evropskimi sodišči v okoljevarstvenih zadevah - Brkan, Maja (Podjetje in delo, 2023)
The paper presents an analysis of the right to access to justice in matters of environmental protection in the case law of the Court of Justice of the European Union, as well as in the jurisprudence of some member states. The first part of the article reviews the recent case law of the Court of Justice of the European Union, on one hand limiting direct access to a European court through a strict interpretation of the Plaumann test, and one the other hand, expending the obligation of member states to, in accordance with the Aarhus Convention, ensure wide access to justice in environmental matters. The second part of the article outlines the possibility of access to justice in the Republic of Slovenia and also presents some of the jurisprudence of national courts of other member states. The objective of the paper is to analyse the effectiveness of the enforcement of the right to access to justice in environmental matters, or more specifically in climate matters, especially in the case of general legal instruments of the EU, through the "comprehensive system of legal remedies" split between national courts and the Court of Justice of the European Union.
Keywords: Aarhuška konvencija; okoljsko pravo; sodišča; Sodišče EU; sodna praksa; varstvo okolja